Closing the Racial Achievement Gap:The Role of Reforming Instructional Practices - Wenglinsky, Harold (Education Policy Analysis Archives, 2004)
No Child Left Behind calls for schools to close the achievement gap between races in math and reading. One possible way for schools to do so is to encourage their teachers to engage in practices that disproportionately benefit their minority students. The current study applies the technique of Hierarchical Linear Modeling to a nationally representative sample of 13,000 fourth graders who took the 2000 National Assessment of Educational Progress in mathematics to identify instructional practices that reduce the achievement gap. It finds that, even when taking student background into account, various instructional practices can make a substantial difference.